Prevalence, Characterization and PFGE profiles of multidrug resistance extended spectrum β-lactamase producing Escherichia coli strains in animal-derived food products from public markets in Eastern Turkey - Cebeci, T (Journal of the Hellenic Veterinary Medical Society, 2022)
Multidrug-resistant (MDR) Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) has increased markedly in recent years, which has currently posed a major challenge in antimicrobial treatments and raised concerns regarding possible transfer of such bacteria through the food chain. The aim of this research was to investigate the prevalence of ESBL-producing E. coli in milk, cheese and meat samples and to determine their virulence, pathotype, serotype, antibiotic resistance and genetic relatedness. A total of 300 food samples were purchased from public markets in different districts of Giresun city. Five (1.6%) of 300 food samples resulted positive for ESBL-producing E. coli isolation. β-Lactamase-encoding genes of the CTX-M (20%), TEM (40%), and SHV (20%) groups were detected singly or in combination. Five ESBL-producing E. coli isolates were further analysed for the presence of virulence genes. Virulence factor genes detected were hlyA (20%), ehlyA (20%), iutA (60%), iucD (40%), fimH (100%), kpsMTII (100%) and traT (100%). Of 130 E.coli isolates, 5 ESBL-producing E. coli strains (totally 3.8%) were isolated, including 3 EHEC (60%). No EIEC, ETEC, EPEC, DAEC or EAggEC3 was detected. In PCR, three stx2 (60%) and one flicH7 (20%) encoding genes were found in ESBL-producing E. coli isolates. In addition, genes encoding Shiga toxins were detected in 3 of 5 isolates, three isolates (60%) encoded O128 serotype.The antibiotic susceptibility test of positive isolates showed resistant to cefuroxime, trimethoprim/ sulfamethoxazole, cefazolin, streptomycin, ceftriaxone, tetracycline, ampicillin and trimethoprim. Most of ESBL-producing E. coli isolates showed 80% MDR phenotypes against at least four classes of antibiotics. Specific-PCR detection of antibiotic resistance genes showed the prevalence of the tetA gene in most of the isolates (80%), followed by dfrA, qnr, aadA1 and sul1. PFGE results show that the isolates from different districts presented no clonal relatedness. This is the first report of the characteristics of multidrug resistance ESBL-producing shigatoxigenic E. coli in dairy and meat products in a local city in Turkey. Our findings indicate that dairy and meat products could be reservoirs of MDR ESBL-producing E. coli strains that were possessed several virulence factors and may be a cause of concern for human health.